A Simply HPLC Method for Determination of Cefpodoxime in Chinese Volunteer and Pharmacokinetic Study - Zhang, J-h.; Guo, S.; Xu, M.; Wu, L-X. (Drug Research, 2013)
A sensitive HPLC method was developed for the determination of cefpodoxime in human plasma. After protein precipitation with acetonitrile, sample was injected into the HPLC system for analysis. The chromatographic separation was carried out on a Diamonsil C18 column with a mobile phase consisting of acetonitrile-water. The mobile phase composed of water (containing 20 mmol/L monoammonium phosphate) and acetonitrile (90: 10, v/v). The detection wavelength was set at 254 nm. The standard curve for cefpodoxime was linear over the concentration range of 0.05–8 μg/mL with a lower limit of quantification of 0.05 μg/mL. The intra- and inter-day RSD values were lower than 10%, and the RE values were within±5%. For the pharmacokinetic analysis of plasma, the mean (SD) values obtained for the formulation were: Cmax, 4.21 (0.62) µg/mL; Tmax, 2.47 (0.61) h; t1/2, 2.38 (0.46) h; AUC0-24 h, 21.13 (3.39) µg/mL/h; and AUC0-∞, 23.34 (3.87) µg/mL/h; MRT, 2.21 (0.41) h, respectively.
Keywords: cefpodoxime; HPLC; pharmacokinetics